Respon Histologis Aorta dan Jantung Rattus Norvegicus Hiperlipidemia Setelah Pemberian Jus Buah Kersen (Muntingia calabura L.) dan Ekstrak Daun Lakum (Cayratia trifolia L.) - Agustina, Enyda; Saraswati, Tyas Rini; Tana, Silvana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2022)
This study aims to determine the histological features of the aorta and heart of male Rattus norvegicus after administration of cherry juice (Muntingia calabura L.) dan lakum leaf extract (Cayratia trifolia L.). The study used 30 male Rattus norvegicus L. in a Completely Randomized Design (CRD) consisting of 5 treatments with 6 repetitions, namely the control group (P0), the standard feeding group (P1), the hyperlipid feed group + 0.2 mL/200 g BB cherry juice (P2), the hyperlipid feed group + 40 mg / 200 g BB lakum leaf extract (P3) and hyperlipid feed group + 0.18 mg / 200 g BB simvastatin (P4). Hyperlipid feed was given during the treatment, which was 28 days. To obtain histological data, preparations were made using the paraffin method and then observed using a photomicrograph with 400x magnification and observing the aortic lumen, foam cells and intracellular accumulation of lipids in smooth muscle. Data were analyzed by ANOVA followed by Duncan Test at a significant level of 5%. The results showed that the addition of cherry juice and lakum leaf extract gave a significant effect on lumen width and thickness of the aortic wall (p <0.05), while on changes in heart muscle cell size no significant effect (p> 0.05). Histomorphometri showed the presence of foam cells and accumulation of smooth muscle lipids in the control and group treatments with hyperlipid feeding. The conclusion of this study was that the addition of cherry juice and lakum leaf extract can reduce atherosclerotic lesions by eliminating showed foam cells and prevent proliferating smooth muscle cells so the size of the aortic lumen width returns to normal, but didn’t cause enlargement of the heart muscle (cardiomegaly).